The SPES facility at Legnaro National Laboratories. (December 2020) - Marchi, T; Prete, G; Gramegna, F; Andrighetto, A; Antonini, P; Ballan, M; Bellato, M; Bellan, L; Benini, D; Bisoffi, G; Bermudez, J; Benzoni, G; et al.
Abstract: Worldwide efforts to tackle the nature of exotic nuclei comprise the construction of new-generation Radioactive Ion Beam facilities. The Italian community is deeply involved in the process and the construction of SPES at Legnaro National Laboratories (INFN) is progressing. This contribution describes the layout of SPES in all its flavours, from Nuclear Physics to Applications in Nuclear Medicine and Neutron Physics. In particular, the status of the SPES-β ISOL facility, together with some of the relevant physics cases and the associated equipment are described.